2017
DOI: 10.1080/1547691x.2017.1414339
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous nanocellulose, crystalline nanocellulose, carbon nanotubes, and crocidolite asbestos elicit disparate immune responses upon pharyngeal aspiration in mice

Abstract: With the rapid development of synthetic alternatives to mineral fibers, their possible effects on the environment and human health have become recognized as important issues worldwide. This study investigated effects of four fibrous materials, i.e. nanofibrillar/nanocrystalline celluloses (NCF and CNC), single-walled carbon nanotubes (CNTs), and crocidolite asbestos (ASB), on pulmonary inflammation and immune responses found in the lungs, as well as the effects on spleen and peripheral blood immune cell subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 54 publications
0
48
0
Order By: Relevance
“…While currently there are no published data revealing a safety concern for nanocellulose in the workplace or in consumer products, experimental evidence has been collected for the potential hazardous effects of CNCs and CNFs . While most cellular studies have addressed cytotoxicity, inflammation and genotoxicity, which can be related to differences in the cellular uptake of CNCs versus CNFs or their ability to generate oxidative stress, most in vivo studies have focused on the effects in the lung and the reproductive system . For instance, pulmonary exposure to CNCs is capable of generating dose‐dependent pro‐inflammatory effects and oxidative stress, while CNFs are capable of inducing TH1 polarizing effects in the lung .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While currently there are no published data revealing a safety concern for nanocellulose in the workplace or in consumer products, experimental evidence has been collected for the potential hazardous effects of CNCs and CNFs . While most cellular studies have addressed cytotoxicity, inflammation and genotoxicity, which can be related to differences in the cellular uptake of CNCs versus CNFs or their ability to generate oxidative stress, most in vivo studies have focused on the effects in the lung and the reproductive system . For instance, pulmonary exposure to CNCs is capable of generating dose‐dependent pro‐inflammatory effects and oxidative stress, while CNFs are capable of inducing TH1 polarizing effects in the lung .…”
Section: Discussionmentioning
confidence: 99%
“…While most cellular studies have addressed cytotoxicity, inflammation and genotoxicity, which can be related to differences in the cellular uptake of CNCs versus CNFs or their ability to generate oxidative stress, most in vivo studies have focused on the effects in the lung and the reproductive system . For instance, pulmonary exposure to CNCs is capable of generating dose‐dependent pro‐inflammatory effects and oxidative stress, while CNFs are capable of inducing TH1 polarizing effects in the lung . Moreover, pulmonary CNC exposure can exert systemic effects, e.g., influencing sperm counts, mobility, and DNA strand breaks in the male reproductive system .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse effects on spermatogenesis and caudal epididymal sperm in mice administered with CNC for 3 weeks have been documented (Farcas et al, ). Similarly, Park et al () showed that CNC elicited alterations in immune response following pulmonary exposure to BALB/c mice. The toxicity of sulphonated nanocellulose in renal tissue of rats has also been reported (Adewuyi, Otuechere, Adebayo, Anazodo, & Pereira, ).…”
Section: Introductionmentioning
confidence: 86%
“…Pulmonary exposure to NFC led to discrete local immune cell polarization patterns with TH1-like immune reaction, while CNC caused non-classical or non-uniform responses. However, the response to both types of nanocellulose was milder than the response to asbestos and carbon nanotubes [276]. In addition, curcumin was able to suppress, at least in part, the immune response to cationic needle-like cellulose nanocrystals, as observed by diminished IL-1β secretion in mouse J774A.1 macrophages primed with LPS [19].…”
Section: Potential Cytotoxicity and Immunogenicity Of Nanocellulosementioning
confidence: 92%